The Effect of Using Sequenced Pictures on Students’ Ability to Write Narrative - Sy, Evha Nazalatus Sa'adiyah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2019)
This study was conducted in order to answer one research question, “Is there any effect of using sequenced picture on the students writing narrative ability at the tenth grade of SMK Bustanudin Pamekasan? This research used quantitative experimental research. The object of this was 25 students at SMK Bustanudin Pamekasan. Before collecting the data, the researcher observed the students to know their levels of English achievement, especially in writing narrative. The ways to collect data that are doing pre-test and doing post-test. Pre-test was given to the object of this study, before they were given treatment. Post-test was given after the researcher conducted the treatments to thestudents. The pre-test was not provided with sequenced pictures. The pre-test required the students write narrative paragraph. The students were supposed to write their favorite story. In the post-test, the student was also asked to write a narrative paragraph based on the sequenced pictures given. The treatment was given after pre-test by the teacher. The teacher taught narrative text by using picture of sequence to see the difference of students’ ability in writing narrative paragraph. The sequenced pictures were used as a media in teaching learning process for the length of pre-test and post-test. The result of data analysis turned out to prove that there was a significant different between the mean score of the pre-test (60) and the post-test (73). In fact, the mean score of the post-test was significantly higher than that of the pre-test. The result of t-test (10.670) was higher than t-table (2.064) for .05 percent level and (2.797) for .01 percent level). it can be concluded that sequenced pictures help students achieve better performance in writing narrative.